Alternative Fuel from Agricultural Waste - Sahu, Om Prakash (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
Waste can be minimized by reuse or recover by the process due disposal of the waste is big issue for environment. So many organization are working for to utilized the waste for energy recovery. Field crops offer potential source of fuel, offering promise as large-scale energy and based on its genetic diversity, climatic adaptation, and biomass and sugar production. Lignocellulosic biomass is the most abundant organic raw material in the world. Production of ethanol from renewable lignocellulosic resources may improve energy availability, decrease air pollution and diminish atmospheric CO2 accumulation. Presently this work was to evaluate the feasibility of ethanol production and optimization from Rice husk by using commercial bakery yeast, i.e., S. cereviciae. The experiment was conducted, at fermentation temperature 30°C and pH 5, and treated using different acid concentrations and residence times. Rice husk was hydrolyzed by refluxing, a solid to liquid ratio of 1:10, using dilute sulfuric acid (1 to 5 %) and distilled water at hydrolysis time of 1 to 11 hours keeping boiling temperature. 90 % maximum total sugar concentration was obtained at 5 h acid free hydrolysis. Based on these hydrolysis results, fermentation process was performed.